State, Social Movements and Agrarian Reform: The Two Phases in Celso Furtado’s Thought before 1964 - e Souza, Julia Gomes (Pontifícia Universidade Católica de São Paulo, 2007)
The present work studies important aspects of Celso Furtado’s thought prior to the military coup of 1964. This article highlights the regional question and, within it, the agrarian reform issue in order to encourage the debate on the relationship between State and social movements.